Enhancing titers and productivity of rCHO clones with a combination of an optimized fed-batch process and ER-stress adaptation - Chandrawanshi, Vikas; Kulkarni, Rohan; Prabhu, Anuja; Mehra, Sarika (Journal of Biotechnology, 2020)
To increase the productivity of rCHO cells, many cell engineering approaches have been demonstrated that over-express or knockout a specific gene to achieve increased titers. In this work, we present an alternate approach, based on the concept of evolutionary adaptation, to achieve cells with higher titers. rCHO cells, producing a monoclonal antibody, are adapted to ER-stress, by continuous culturing under increasing concentration of tunicamycin. A sustained higher productivity of at-least 2-fold was achieved in all the clones, in a concentration-dependent manner. Similarly, a 1.5-2 fold increase in final titers was also achieved in the batch culture. Based on metabolic analysis of the adapted cells, a fed-batch process was designed where significantly higher titersare achieved as compared to control. Metabolic flux analysis is employed in addition with gene expression analysis of key genes to understand the basis of increased performance of the adapted cells. Overall, this work illustrates how process modifications and cellular adaptation can be used in synergy to drive up product titers.
Keywords: Adaptive laboratory evolution; CHO cells; ER-stress; Fed-batch; Increased productivity and titers; Recombinant protein production; UPR pathway